Underage drinking as a natural part of growing up: a UK study of parental beliefs. Issue 3 (3rd June 2019) - Fulton, Emily; Baines, Darrin; Bartle, Naomi
Abstract : Purpose: Parental beliefs about underage drinking are known to influence the drinking behaviours of their children. The purpose of this paper is to explore parental beliefs about their own child drinking alcohol and young people in general, in order to ascertain whether there is a need to target such beliefs in the design of public health interventions. Design/methodology/approach: Parents of 11–18 year olds attending one of nine schools in the Midlands of England, UK were invited to take part. Participants completed a newly designed 40-item questionnaire measuring parental beliefs about the impact and causes of underage drinking; talking to their child about alcohol; and how much and how often they thought their child consumed alcohol. Findings: In total, 185 parents took part in the study, reporting on their eldest child aged 18 or under. The majority of parents agreed that underage drinking is detrimental to child health and wellbeing. However, over 60 per cent believed that alcohol consumption is a "natural part of growing up", and stronger agreement with this belief was associated with higher parental reports of alcohol consumption in their children. Social implications: The majority of parents recognised the risks and negative effects of alcohol; however, many also believe it is a natural part of growing up. Parents may hold conflicting beliefs about underage drinking, which could impact on the drinking beliefs and behaviours of their children. Originality/value: Public health interventions may need to counter the common parental belief that underage drinking is a normal part of growing up and therefore to be expected. Clear messages about the impact parent beliefs and behaviour have on young people drinking, to ensure parents recognise that messages are aimed at themselves, and not just "other parents" are imperative.